Fingerprinting of gelatinase subtypes for different topographic regions on non-retaining placenta of Holstein cows. (17th October 2014) - Piamya, P.; Tiantong, A.; Chen, S.-E.; Liu, W.-B.; Yu, C.; Nagahata, H.; Chang, C.-J.
Abstract : The contribution of matrix metalloproteinases (MMP) to timely discharge of the placenta from bovine uterus at parturition is yet inconclusive, partly because of the presence of multiple MMP forms in situ . In the current study, the expression of different gelatinase subtypes on non-retaining placentas of Holstein cows was fingerprinted by using gelatin zymography. Different topographic regions on the placenta were measured separately, including the placentome-like structure and the fetal and maternal sides of interplacentomal placenta, all sampled from the central and peripheral areas of the placenta, respectively. The spontaneously ruptured umbilical cords were cross-sectioned as fetus end, middle and placenta end also for separate measurement. Body fluids including blood samples from the parturient cows, their neonatal calves and umbilical cord, as well as fetal fluids and the first colostrum were measured concomitantly. Results showed multiple forms of gelatinases subtypes in the placenta tissues and body fluids, including neutrophil gelatinase-associated lipocalin (NGAL)-MMP-9 complex, both the latent and active forms of MMP-2 and MMP-9; of them, the latent forms were much more abundantly and frequently expressed than the active forms. NGAL-MMP-9 complex was more prevalently present in the body fluids than in the placenta tissues. No distinguishable pattern of the expression of any gelatinase subtype was observed among the placentome-like structure, interplacentomal placenta and umbilical cord, or between fetal and maternal sides. Nonetheless, for interplacentomal placenta, proMMP-9 expression was higher in the central than in the peripheral area. In addition, proMMP-2 expression was higher in the rupture end (fetus end) than the placenta end of the umbilical cord. In conclusion, the current validated gelatin zymography detected a gradient proMMP-9 expression on the non-retaining placenta of cows in reverse to the proximity to the umbilical insertion point, and a gradient proMMP-2 expression on a section of the umbilical cord in reverse to the proximity to the rupture site, suggesting roles played by gelatinases in normal discharge of the placenta at term.